Using New Hampshire Colonoscopy Registry data to assess United States and European post-polypectomy surveillance guidelines - Liu, Margaret C.; Anderson, Joseph C.; Hisey, William; MacKenzie, Todd A.; Robinson, Christina M.; Butterly, Lynn F. (Endoscopy, 2023)
Background Our goal was to compare the updated European Society of Gastrointestinal Endoscopy (ESGE) and United States Multi-Society Task Force on Colorectal Cancer (USMSTF) high risk groups in predicting metachronous advanced neoplasia on first follow-up colonoscopy and long-term colorectal cancer (CRC).Methods We compared advanced metachronous neoplasia risk (serrated polyps ≥ 1 cm or with dysplasia, advanced adenomas [≥ 1 cm, villous, high grade dysplasia], CRC) on first surveillance colonoscopy in patients with high risk findings according to ESGE versus USMSTF guidelines. We also compared the positive and negative predictive values (PPV, NPV) of both guidelines for metachronous neoplasia.Results The risk for metachronous neoplasia in our sample (n = 20 458) was higher in the high risk USMSTF (3 year) (13.6 %; 95 %CI 12.3–14.9) and ESGE groups (13.6 %; 95 %CI 12.3–15.0) compared with the lowest risk USMSTF (5.1 %; 95 %CI 4.7–5.5; P < 0.001) and ESGE categories (6.3 %; 95 %CI 6.0–6.7; P < 0.001), respectively. Adding other groups such as USMSTF 5–10-year and 3–5-year groups to the 3-year category resulted in minimal change in the PPV and NPV for metachronous advanced neoplasia. High risk ESGE (hazard ratio [HR] 3.03, 95 %CI 1.97–4.65) and USMSTF (HR 3.07, 95 %CI 2.03–4.66) designations were associated with similar long-term CRC risk (CRC per 100 000 person-years: USMSTF 3-year group 3.54, 95 %CI 2.68–4.68; ESGE high risk group: 3.43, 95 %CI 2.57–4.59).Conclusion Performance characteristics for the ESGE and USMSTF recommendations are similar in predicting metachronous advanced neoplasia and long-term CRC. The addition of risk groups, such as the USMSTF 5–10-year and 3–5-year groups to the USMSTF 3-year category did not alter the PPV or NPV significantly.